Experimental Study of the Heat Transfer During the Ice Formation of tio2 Water-Nanofluid Around a Helical Coil Ctes System - Chen, D; Nunez-Aedo, J; Martinez-Gutierrez, V; Vasco-Calle, D (Elsevier Ltd, 2023)
Attending to the increasing energy consumption, the interest in Cooling Thermal Energy Storage (CTES) has grown since its application might enhance the performance of refrigeration systems by storing thermal energy at low temperatures via ice-making. CTES is essential in many applications, including central air conditioning in buildings, high-powered electronic cooling applications, waste heat recovery, and food processing, to correct the imbalance in electrical power between daytime demand and nighttime abundance. Regarding air conditioning, CTES releases cool energy through ice melting to support the primary chilling equipment throughout the day, regarded as the peak period. Following this path, this work contributes to the existing bench-scale results in the literature by performing a comparative analysis of the thermal performance of CTES systems operating with water and a 0.19 vol.% TiO2 water-based nanofluid as phase change material (PCM). The bench scale CTES system is an insulated rectangular-shaped tank filled with 36 liters of PCM flooding a helical coil. Since a water/alcohol mixture was the coolant, the temperature of the helical coil allowed ice to grow around itself. The CTES with 0.19 vol.% TiO2 nanofluid results in an 11.1% larger amount of ice and a faster charging process (10.6%). Moreover, the heat transfer process observed on the CTES system operating with the nanofluid has improved the system s maximum energy storage rate by 17.18%. Analyzing the heat transfer process by computing the involved thermal resistances has allowed explaining the observed improvements. Based on this thermal analysis, we have identified that TiO2 nanoparticles mainly affect the natural convection between the ice layer and the liquid phase of the PCM by increasing the convective heat transfer coefficient. © 2023 Elsevier Ltd